2001
DOI: 10.1159/000051629
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Posture and Gravitational Forces on Shear Wave Propagation in the Skin

Abstract: The body posture and gravitational forces govern in part the intrinsic skin tensile strength because they influence the orientation of the dermal fibre networks. Our objective was to assess changes in shear wave propagation in the skin according to the body posture and orientation of the gravitational forces. The study was performed in 30 middle-aged women with a normal body mass index. The Reviscometer® was used to assess the mechanical wave propagation on the volar forearm in extension or flexion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 8 publications
3
46
0
4
Order By: Relevance
“…The time the waves needs to travel from the transmitter to the receiver is the RRTM expressed in arbitrary units. The instrumental variability tested on human skin was lower than 14% (Nizet et al, 2001) while it averaged to 1.2% on a silicone gel.…”
Section: Volunteers and Methodsmentioning
confidence: 82%
See 3 more Smart Citations
“…The time the waves needs to travel from the transmitter to the receiver is the RRTM expressed in arbitrary units. The instrumental variability tested on human skin was lower than 14% (Nizet et al, 2001) while it averaged to 1.2% on a silicone gel.…”
Section: Volunteers and Methodsmentioning
confidence: 82%
“…The Reviscometer ® is a new device for measuring the shear wave velocity in the skin (Nizet et al, 2001). The speed of propagation of the acoustic wave on the skin surface is inversely proportional to the stiffness and density of the tissues (Potts et al, 1983(Potts et al, , 1984Davis et al, 1989;Vexler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a finding suggests increased firmness or tensor effect, since the speed of shear wave propagation on the skin surface is directly proportional to its stiffness (Ruvolo, Stamatas, Kollias, 2007;Vexler, Polyansky, Gorodetsky, 1999). In rigid skin the time for wave spreading will be short, anisotropy and RRTM values smaller (Nizet, Pierard-Franchimont, Pierard, 2001;Verhaegen et al, 2010). Ruvolo, Stamatas and Kollias (2007) and Hermanns-Lê et al (2001) observed that while the minimum RRTM values remained fairly constant for the different age groups, the maximum RRTM values increased with age.…”
Section: Corneometermentioning
confidence: 96%